Spravedlnost dekonstrukce, dekonstrukce spravedlnosti. K Derridově koncepci spravedlnosti - Miroslav Vacura (Právněhistorické studie, 2024)
The study is devoted to Derrida’s conception of normativity, focusing on his intervention in jurisprudence through reinterpretation of the concept of justice, which had a major influence on American critical legal studies theorists. A short introduction setting the topic into a broader context is followed by a section providing a brief overview of Derrida’s essential conceptual apparatus and the explanation of the method of deconstruction. In the next section, we identify two complementary ways in which Derrida understands the concept of justice: the first identifies justice directly with deconstruction, and thus centers normativity in Derrida’s own philosophical project; the second connects the concept of justice to the idea of infinity, and thus refers to Lévinas’ philosophy. In the conclusion of the text, we summarize the most significant responses and critical reactions to Derrida’s conception and consider whether it can provide guidance for judicial decision-making, as some theorists have suggested.